2018
DOI: 10.1111/sed.12441
|View full text |Cite
|
Sign up to set email alerts
|

Facies model of a mixed clastic–carbonate, wave‐dominated open‐coast tidal flat (Tithonian–Berriasian, north‐east Spain)

Abstract: Detailed logging and analysis of the facies architecture of the upper Tithonian to middle Berriasian Aguilar del Alfambra Formation (Galve sub-basin, north-east Spain) have made it possible to characterize a wide variety of clastic, mixed clastic-carbonate and carbonate facies, which were deposited in coastal mudflats to shallow subtidal areas of an open-coast tidal flat. The sedimentary model proposed improves what is known about mixed coastal systems, both concerning facies and sedimentary processes. This se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…18). Spatial patterns summarized here are similar to carbonate-rich tidal flats adjacent to siliciclastic-rich tidal flats documented in Spain by Bádenas et al (2018). Schwartz et al (2018) also found a wide array of contemporaneous mixed carbonate-siliciclastic environments in the Neuquén Basin of Argentina, and postulated that the variety and complexity of mixed carbonatesiliciclastic settings are related to both the proportion of carbonate and siliciclastic production, and such dominant marine transport processes as storm, shelf, and tidal currents.…”
Section: High Lateral Facies Variability At Bedform Outcrop and Bassupporting
confidence: 77%
See 1 more Smart Citation
“…18). Spatial patterns summarized here are similar to carbonate-rich tidal flats adjacent to siliciclastic-rich tidal flats documented in Spain by Bádenas et al (2018). Schwartz et al (2018) also found a wide array of contemporaneous mixed carbonate-siliciclastic environments in the Neuquén Basin of Argentina, and postulated that the variety and complexity of mixed carbonatesiliciclastic settings are related to both the proportion of carbonate and siliciclastic production, and such dominant marine transport processes as storm, shelf, and tidal currents.…”
Section: High Lateral Facies Variability At Bedform Outcrop and Bassupporting
confidence: 77%
“…The model of tidal mixing--along the margins of a geographically restricted tidal strait (Fig. 18) --is similar to the tidal mixing model of Bádenas et al (2018) in the Mesozoic Galve Sub-basin, Spain, though the sediments deposited in the open coast tidal setting of that study were more influenced by storms and waves than the sediments of the Bouse Formation.…”
Section: Sedimentary Hydrodynamicssupporting
confidence: 61%
“…The tempestite succession is overlain by bioturbated quartz arenites of the shoreface, and topped by the bar-trough systems of the cross-bedded quartz arenites of the upper shoreface zone. Fairly thick storm bed successions require subsidence of the basin and high rates of sedimentation that preserved the tempestites from reworking by fair-weather waves, tides and subsequent storm erosion (Einsele, 2000, Bádenas et al, 2018. The required subsidence developed during the Frasnian, when a bulge area evolved north of the study area on the inner part of the Cantabrian Zone and downwarping of the surrounding shelf area occurred in the External Zone.…”
Section: Mixed Inner Shelf-siliciclastic Middle Shelf-mixed Outer Shelfmentioning
confidence: 99%
“…2, 3a) by Mas et al (2004). However, recently, Aurell et al (2016), Bádenas et al (2018) and Val et al (2019) have subdivided the deposits traditionally considered as belonging to the Villar del Arzobispo Fm in the Galve sub-basin (see references cited in the previous paragraph), in three formal units, which Aurell et al (2016) extend to the western Peñagolosa sub-basin. These units are ( Fig.…”
Section: The Lithostratigraphic Framework Of the Dsr In The Western Mmentioning
confidence: 99%